Transformation Programs: Content and Sequencing - Dhanji, Farid (American Economic Review, 1991)
Conventional wisdom will have it that Poland opted for a dramatic, compressed dash towards market capitalism-a Big Bang that in one stroke shed central planning and dismantled bureaucratic interference in large areas of economic decision making. Hungary, it is believed, has taken a more gradual, time-consuming, less forced approach towards the same end. These perceived contrasts in strategy (shock therapy vs. gradualism) are keenly debated in policy reform circles throughout the region, both with respect to necessity as well as to feasibility. The conventional wisdom greatly simplifies the contrast between the two countries. Recent political developments in Hungary have generated a substantial acceleration of reform efforts. The Hungarian reform program now operates on as broad a front as the Polish program: abandonment of central controls, price liberalization, introduction of competition, privatization, financial and fiscal system modernization, development of social safety nets, legal, regulatory and institutional reform, and so on. It seeks a no less fundamental and far-reaching change. The perception of gradualism probably has more to do with the past 20 years of Hungarian experimentation with piecemeal modifications to the economic mechanism (Janos Kornai, 1986) than to the present reality. That past experience certainly suggests that without genuine political commitment to a market economy, and particularly to a broad-based system of private property rights, systemic reforms in formerly socialist economies will not succeed. Once these precepts are accepted, the specific agenda items for reform appear to take on the same character in all reforming economies. The pace and sequencing of economic and institutional changes are then dictated by initial starting conditions that differ greatly between countries (Stanley Fischer and Alan Gelb, 1990). Price liberalization and the dismantling of central coordination can be accomplished overnight; the establishment of new legal systems, privatization, the restructuring of enterprises, generating attitudinal and behavioral changes in populations, all perforce take much longer. As a result, it may be expected that the ambit for genuine choices on pace and sequencing on policy and institutional change will narrow over time and that the content of reforms in Hungary and Poland and other countries will increasingly resemble one another.